Toward Modernization and Internationalization (M&I) of Higher Education Institution - Gembong Baskoro (Institute of Research and Community Outreach - Petra Christian University, 2011)
Knowledege based economy will be a matter of time for Indonesia’s future competitiveness. Therefore, to get there, several basic requirements have to be early prepared. Among others, human capital is perhaps the most important requirement for a country to be able to develop an economic condition based on the capability and capacity of knowledge. Human capital is not just Indonesia concern, it is the concern of all countries. In fact, only some countries can create a condition for human capital to grow effectively and efficiently. Mostly, Higher Education Institution (HEI) or university is the main organization that has objective to develop human capital. The pupose of HEI is to develop academic and non-academic capability for student by mean of educating them with a structured curriculla. However, in today’s environmental condition even with similar curriculla, any HEI may ends up with different quality. From this point of view, this paper will discuss and elaborate further on a policy and strategy that enable a HEI can create a competitive education environment for student to grow up to their best competitive conditions.